SUBSTITUTION OF SOLVENT-BASED SYSTEMS WITH WATER-BASED IN THE TOPCOAT FINISHING OF LAMINATED FOIL LEATHER - Nely Cahyani; Atiqa Rahmawati; Emiliana Anggriyani (Politek ATK Yogyakarta Press, 2025)
Laminated leather is widely used types of leather due to its appealing surface appearance and mechanical durability. However, the conventional top-coating process of laminated leather typically employs solvent-based compounds such as butyl acetate, which contain volatile organic compounds (VOCs) that contribute to environmental pollution and health hazards. The substitution of solvent-based with water-based formulations in the top coat represents an important step toward more sustainable and eco-friendly leather manufacturing practices. In this study, leather samples were prepared and subjected to three different treatments: K1 (water-based), K2 (solvent-based), and K3 (without solvent). The finishing stages included milling, buffing, foil lamination, additional milling, and top coat spraying. The finished leathers were evaluated organoleptically through several assessments, including foil adhesion, surface gloss, surface texture, and color shift analysis. The findings revealed that the type of top coat significantly affected both the visual and adhesive properties of the laminated leather. The water-based top coat produced a slightly rougher surface with lower gloss and a darker tone, while the solvent-based top coat resulted in a smoother, glossier finish that retained the leather’s original color. Furthermore, the water-based top coat exhibited the highest foil adhesion strength, achieving an average score of 3.7 (on a scale of 4), compared to 2.6 for solvent-based and 1.0 for untreated samples. These results indicate that water-based top coats can effectively enhance foil adhesion while reducing the environmental impact, making them a promising alternative for sustainable laminated leather finishing in upper shoe production.